PRACTICAL SIGNIFICANCE OF INCLUSIVE EDUCATION - Raxmanova Shaxnoza Abdivayitovna; Mitalova Nargiza Salibayevna (Modern American Journals, 2025)
Inclusive education is a modern approach that allows all children, including those with disabilities or special needs, to learn together in the same classroom. It promotes equality, respect, and cooperation among students. The practical significance of inclusive education is that it helps children develop social skills, tolerance, and empathy. Teachers also become more flexible and creative in their teaching methods. Inclusive education benefits not only students with special needs but also their classmates by creating a positive and supportive learning environment. Therefore, inclusive education plays an essential role in building a fair and understanding society.
Keywords: Inclusive education, equality, diversity, special needs, cooperation, social integration, learning environment.